2008
DOI: 10.1016/j.infbeh.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal sensitivity of preterm versus full-term infants to the effects of maternal depression

Abstract: Comparisons were made of differences in the hormonal sensitivity of preterm versus full-term infants to maternal depression, as reflected in children's cortisol levels. In Study 1 (N = 25), a comparison was made between preterm versus healthy full-term children. In Study 2 (N = 80), a comparison was made between preterm infants and full-term infants with mild or moderate medical problems. Preterm infants were found be highly reactive to maternal depression (as measured by the Beck Depression Inventory). That i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
3
26
0
2
Order By: Relevance
“…In addition, this study did not include the measurement of some outcome measures previously studied by other authors, such as NBI cortisol levels, and caregiver resilience. [27][28][29] Otherwise, some of the strengths of this study were that it allowed caregivers to self-complete the depressive symptom report scales, and the inclusion of a structured survey to explore outcome measures of interest. In addition, the detection of factors associated with depressive symptoms in the population of developing countries is actually useful to improve the interdisciplinary management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study did not include the measurement of some outcome measures previously studied by other authors, such as NBI cortisol levels, and caregiver resilience. [27][28][29] Otherwise, some of the strengths of this study were that it allowed caregivers to self-complete the depressive symptom report scales, and the inclusion of a structured survey to explore outcome measures of interest. In addition, the detection of factors associated with depressive symptoms in the population of developing countries is actually useful to improve the interdisciplinary management.…”
Section: Discussionmentioning
confidence: 99%
“…Poehlmann and Fiese (2001) found that elevated, but subclinical, maternal depressive symptoms significantly predicted insecure attachment in preterm, but not in full-term, infants. Recently, Bugental, Beaulieu, and Schwartz (2008) found that cortisol levels in preterm infants were more affected by maternal depression compared to full-term infants. However, stable elevations in maternal depressive symptoms have been associated with problematic outcomes in children and adolescents born healthy and full-term as well (Campbell et al, 2009).…”
Section: Maternal Depressionmentioning
confidence: 99%
“…9 Preterm infants appear more sensitive to the impact of poor maternal mental health as compared to full term infants. 10, 11 …”
Section: Introductionmentioning
confidence: 99%